2004
DOI: 10.14429/dsj.54.2049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on Liner Properties of Case-bonded Composite Propellants

Abstract: A thin layer of liner is applied to ensure a good bond between the insulator and the propellant in case-bonded rocket motors. It also acts as a protective shield for the insulator by providing a limited fire protection effect. Liner compositions should preferably be based on the same binder system used in the propellant formulations. As the liner has to hold the propellant and the insulator without debond under all the environmental conditions, it plays a key role in predicted performance of a rocket motor. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, the interaction between various factors is yet to be studied. Experimental results indicate that the failure is either the cohesive within the propellant near the interface or the adhesive fracture [13,15,19]. The former type is exactly what we expect since it indicates a strong adhesive bonding.…”
Section: Measurement Of Adhesive Propertiesmentioning
confidence: 66%
See 1 more Smart Citation
“…However, the interaction between various factors is yet to be studied. Experimental results indicate that the failure is either the cohesive within the propellant near the interface or the adhesive fracture [13,15,19]. The former type is exactly what we expect since it indicates a strong adhesive bonding.…”
Section: Measurement Of Adhesive Propertiesmentioning
confidence: 66%
“…Later, Yin and Wang [17] reviewed the influence factors, in terms of insulation, liner, propellant, and manufacturing process. Since then, more in-depth investigations still focus on the mechanical and adhesive characteristics of the liner due to the effect of particle size of ammonium perchlorate (AP) [18], additives [19], ingredient migration [20], humidity [21] and curing state of liner [22]. By now, the impact of an individual factor has been investigated comprehensively.…”
Section: Measurement Of Adhesive Propertiesmentioning
confidence: 99%
“…The safety of hydroxyl‐terminated polyether (HTPE) propellant with nitroglycerin (NG) replaced by N‐butyl‐N‐nitratoethyl nitramine (NENA) has been greatly improved, but the problems of interfacial adhesion in such charge structure still remain, because of the large polarity difference between the propellant/liner. Maintaining the structural integrity of charge is one of the most challenging issue in SRMs 3–5 . Currently, about one‐third of solid rocket launch accidents are caused by the debonding of the charge structure interfaces, and the integrity of the charge structure has become the main technical bottleneck restricting the development of SRM technology.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, scholars have proposed several strategies to improve the interfacial adhesion properties and inhibit the migration of plasticizers, and have set up related theoretical models 18 . For example, some scholars 4 improved the bonding performance by using the same binder as the propellant as the lining material, but at the same time this led to enhanced migration of plasticizer. Others 19,20 tried to reduce the diffusion coefficient by modifying the molecular structure of plasticizer, but it also decreased the plasticization efficiency and adversely affected other properties of the propellant.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, many factors affect the interfacial bonding property between liner and propellant [5]. Among those factors, heat insulation layer is the major factor effecting the bonding property [6]. The insulation layer contains active groups, such as hydroxyl groups that can adsorb water molecules and at the same time can absorb isocyanate compounds [7,8].…”
Section: Introductionmentioning
confidence: 99%